Single Nucleotide Polymorphisms (Snps) Of Low-Density Lipoprotein Receptor Gene (Ldlr) In Lipid Related Gene-Associated Familial Hypercholesterolaemia Among Iban And Bidayuh Ethnic Groups In Sarawakian Population: Preliminary Data Analysis - Y.T, Siaw; H.H, Hood; S. P, Sim; H., Helmy; M. M., Aminudin (Centre for Pre-University Studies, 2015)
Objectives: Familial Hypercholesterolaemia (FH) is a genetic disease caused by defects in a number of variants, including low-density lipoprotein receptor gene (LDLR) that regulate plasma LDL-cholesterol concentrations. FH typically passed down through families in an autosomal dominant manner. That means one only needs to acquire the abnormal gene from one parent in order to be affected by the disease. FH has a worldwide prevalence of 0.2%, however it is considerably higher in some population because of a founder effect. This study was initiated as there is no FH data available in Sarawak. We aimed to determine the frequencies lipid related gene polymorphisms in Iban and Bidayuh ethnic groups in Sarawak, and its associations with lipid profiles.